AYURVEDIC MANAGEMENT OF CERVICAL EROSION THROUGH YONIDHAVAN WITH TRIPHALA AND DARUHARIDRA KWATH, APAMARGA KSHAR PRATISARAN WITH JATYADI TAILPICHU – A CASE STUDY (AYUSHDHARA, 2020)
In chronic cervicitis, there is marked thickening of the cervical mucosa with underlying tissue oedema. These thickened tissues tend to push out through the external os along the direction of least resistance. The entity is most marked where the cervix has already been lacerated. In such conditions, the longitudinal muscle fibres are free to act unopposed. As a result, the lips of cervix curl upwards. Now a days number of females has developed cervicitis very fast and symptoms are like per vaginal white discharge with foul smell, and dyspareunia. This cervical erosion further leads to dyspareunia and then to infertility also. There is no disease given in Ayurveda classics which can directly correlate with cervical erosion. But in some aspect of symptoms and signs this can correlate with Karnini yonivyapad and hence treatment can be according to that. In this article case study of cervical erosion described which was treated with Ayurvedic Sthanik chikitsa- Yonidhavan by Triphala and Daruharidra kwath, Apamarga kshar pratisaran and Jatyadi tail pichu for 7 days for 3 conjugative cycles. With this combined therapy of Sthanik chikitsa cervical erosion has been completely cured. Hence clinical trial can be done in large number of patients to see further results.